Lignin coating to quench photocatalytic activity of titanium dioxide nanoparticles for potential skin care applications1. Issue 71 (2nd August 2015) - Morsella, M.; Giammatteo, M.; Arrizza, L.; Tonucci, L.; Bressan, M.; d'Alessandro, N.
<x xml:space="preserve">Abstract</x> Ultraviolet light can cause photodamage to the skin, such as sunburn and melanomas.